2022
DOI: 10.1007/s40368-021-00688-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the building blocks of the paediatric dentistry curriculum for undergraduate students in an Australian University

Abstract: Purpose To investigate the attitude of final-year dental students towards their paediatric dentistry training and their confidence in treating child patients. Methods A 55-item questionnaire was distributed online and physically to the final-year BDSc (Hons) students at The University of  Queensland (Australia). The questionnaire consisted of four parts including theoretical knowledge, clinical observational experience, preclinical training and clinical training in paed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Previous international literature has identified that the management of dental trauma is an aspect of pediatric dentistry in which students are the least confident 21 . For all three questions regarding dental trauma, both dental students and graduates reported low levels of confidence.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Previous international literature has identified that the management of dental trauma is an aspect of pediatric dentistry in which students are the least confident 21 . For all three questions regarding dental trauma, both dental students and graduates reported low levels of confidence.…”
Section: Discussionmentioning
confidence: 90%
“…Previous international literature has identified that the management of dental trauma is an aspect of pediatric dentistry in which students are the least confident. 21 For all three questions regarding dental trauma, both dental students and graduates reported low levels of confidence. Dental trauma is an emergency management procedure; thus, many students do not get an opportunity to manage acute care while in dental school.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…ECC management can be impractical on dental chair, largely due to the limitations of patient co‐operation. 10 Other factors include the confidence of the dental practitioners, 11 primary carer preferences, 12 and may require multiple visits. For these reasons, dental general anaesthesia (DGA) has been a traditional management option to provide comprehensive dental caries treatment, particularly when multiple carious teeth needed be treated in one visit.…”
Section: Introductionmentioning
confidence: 99%